NATURAL POLYACETYLENE COMPOUNDS - A. M. Nasukhova; D. A. Konovalov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
In article the review of the initial stage of researches of natural polyacetylene compounds is resulted. The high reactionary ability leading to fast oxidation and degradation of these compounds, especially at influence of Uf-light, oxygen of air, pH and other factors, has caused the serious difficulties connected with an establishment of structure and studying of their physical and chemical properties. Therefore the greatest quantity of works of this stage is connected with studying of essential oils of plants from families Apiaceae, Araliaceae, Asteraceae, Campanulaceae, Olacaceae, Pittosporaceae and Santalaceae where have been found out, basically, diacetylene compounds. About development of physical and chemical methods of the analysis of possibility of similar researches have considerably extended. More than 2000 polyacetylenes are known today, from them more than 1100 are found out in plants fam. Asteraceae. Revolution in the field of molecular biology has allowed to study processes of biosynthesis of these compounds intensively.